Metode Penemuan Terbimbing (Guide Discovery) untuk Meningkatkan Hasil Belajar Konsep Tekanan - Gunawan (Sekolah Tinggi Ilmu Tarbiyah (STIT) Pemalang, 2015)
The many concepts and formulas of pressure that students must master in Science Subjects are very burdensome for students when the learning process only accepts material, notes and memorizes formulas and symbols of magnitude. This results in low mastery of concepts in students, thus encouraging and encouraging teachers to choose the right method in the learning process. One of them is the use of Guided Discovery methods. The results of this study showed that there was an increase in achievement, from 38 students of grade VIIIB in the initial condition who were able to get a KKM score of 17 students or with an achievement of 44.7%, in cycle I there were 24 students or gained 63.2% and in the second cycle were 31 students or achieved 81.6% learning achievement. The conclusion of this research is the use of Guided Discovery method can improve the learning outcomes of the concept of pressure in class VIII B students of SMPN 2 Ampelgading in the academic year 2013/2014.